Yield enhancement with Six Sigma methodology in spindle motor hub assembly for hard disk drive production - Seetal, Intharachot; Thepmanee, Teerawat; Pannil, Pittaya (My University, 2017)
This paper presents a systematic improvement using Six Sigma methodology for increasing process yield in a spindle motor hub assembly for hard disk drive (HDD) production. A data-driven DMAIC (Define, Measure, Analyze, Improve, Control) approach is utilized to improve the existing process for press fitting a hub assembly into a bearing assembly. A Six Sigma defect is defined as any hub/bearing assembly that fails the axial run-out testing for high rotational speed of 7,200 rpm. Optimization of process parameters for defect reduction to enhance process yield is based on the use of Minitab software with Taguchi method. Statistically significant results confirm that the manufacturing yield can be increased from 99.28% up to 99.78%.
Keywords: DMAIC; Production defect; Six sigma; Taguchi method; Yield enhancement